Ações processuais para tutela da multipropriedade imobiliária - Castello, João Victor Pereira (2022)
Objectives: The research aims to systematize the procedural protection of the modality of time sharing established by Law nº. 13.777/2018, which included articles 1.358-B to 1.358-U to the Civil Code (Time-sharing Condominium). Therefore, it is intended to explain the origin, definition, classification and legal nature of time-sharing of real state property, as well as its treatment in countries with the Roman-Germanic legal system and in Brazil. Therefore, it is classified the species of time-sharing in Brazil and its legal nature, so that it is possible to list as appropriate procedure protection for the Condominium in Time-sharing. Thus, it is necessary to examine the sensitive point of the institute – a temporal limitation on the exercise of property rights by the holders of the time-sharing – and its consequences in the causa of action and fulfilling the conditions of the legitimacy and causa and interest to act. At the end, seek to confirm the hypothesis of systematization of procedural protection that corresponds to the peculiarities of the Condominium in Time-sharing. Methodology: Documentary and bibliographic research is carried out, as national and foreign laws, reports, jurisprudence and precedents of the courts and superior courts, legal literature and academic research are analyzed in order to understand the modalities of time-sharing, its legal nature and protection corresponding procedure. In view of the intended approach, the study takes place through the hypothetical-deductive method, since, based on the discovery of the problem – which is the procedural protection adequate to the legal regime of the Condominium in Time-sharing -, a theoretical model of procedural systematization is elaborated, put to the test from a dogmatic application of institutes of the Civil Law and the General Theory of Process. Results: It was possible to conclude that the time-sharing constituted under the terms of arts. 1.358-B to 1358 U of the Civil Code, manifests itself as a way of exercising property. Therefore, it is a real property right, subject to the special regime of condominium in time-sharing, with supplementary and subsidiary application of the Civil Code and Law 4591/1964 (Law on Condominiums in Buildings and Real Estate Developments). Consequently, it becomes possible for the jurisdictional to use adverse possession for the purpose of regularizing the time sharing ownership, making use of interdital protection and other actions that require proof of domain. The study takes care to point out the most sensitive procedural aspects, which concern the cause of action and fulfillment of the conditions of the action. Contributions: The proposed research stands out for presenting the problem from the perspective of forensic practice. Considering that the Brazilian legal literature deals with the time-sharing in a punctual way, with few works dedicated to time-sharing and none that approach it from the procedural aspect, the research innovates by demonstrating that it is possible to systematize the procedural protection of the Condominium in Time-sharing based on its legal nature of real law.